Cybersecurity, digital forensics, and the IoT for deepfake investigation on social media platforms: A review - Abdullah, Ayub Khan; Jamil Alsayaydeh, Jamil Abedalrahim; Laghari, Asif Ali; Bacarra, Rex; Alroobaea, Roobaea; Algarni, Sultan; M. Baqasah, Abdullah (Korea Information Processing Society, 2025)
Numerous privacy and security concerns could jeopardize the social media ecosystem: mishandled hotspot connectivity used as a standalone cybercrime; illegal campaigning; deviant activities conducted online; propagation of anti-national propaganda; and recruitment of terrorists through social media platforms. These provide significant challenges for social media firms and open up new avenues for digital forensics investigations to support analysis and provide answers in the ever-evolving realm of cyber security. However, in terms of logging, inspecting, assessing, storing, presenting, and recording deepfake content, the growth of the Internet of Things has an impact on the cyber forensics’ investigation lifecycle. The integration of IoT with the most recent cyber security frameworks for deepfake analysis in social media platforms is reviewed in detail in this study. We also examine deepfake sounds, movies, and images by reviewing the media forensics literature. We combine the manipulation and alteration that takes place during social media posting for the data modality with an assessment of the technology developments in identifying and measuring manipulation, forgeries, and alterations. In conclusion, this study poses several significant research problems that should be considered, including upholding a safe chain of custody, implementing impersonation countermeasures, and fending against deceptive social engineering tactics